Shrinking areas and mortality: an artefact of deprivation effects?. Issue 11 (18th October 2005) - Exeter, Daniel J; Feng, Z; Flowerdew, Robin; Boyle, Paul J
Abstract : There is evidence that mortality rates are highest in areas that are experiencing population decline, and researchers have recommended that this should be accounted for in health resource allocation. This research finds a significant negative association between population change and mortality for small areas in Scotland, which remains when low social class is accounted for. However, this relation disappears when the area deprivation is accounted for. It is suggested that it is more important to account for deprivation than population change in health resource allocation.